GENDER EQUALITY: SLOW PROGRESS IN CHURCH AND SOCIETY - Cahill, Lisa Sowle (Asian Horizons, 2019)
Pope John Paul II underlined “the equal dignity and responsibility of women with men,” both in society and the family. He also praised “the great process of women’s liberation,” and condemned discrimination against women. Even decades after that, progress worldwide, and in the global Church, has been alarmingly slow. However, there are positive signs. Though Pope Francis continues to espouse a theology of gender complementarity that many find problematic, he still recognizes the need for some new thinking. In spite of resistance, some of the Catholic institutions for theological studies have made considerable progress toward an ecclesial and social praxis of gender equality. The 2010 Gender Policy of the Catholic Church of India is another initiative that deserves to be celebrated; yet its implementation continues to present significant challenges. There are also encouraging models where women and men work for emancipation of women and women create networks for the empowerment of women in other parts of the world. However, even now traditional gender concepts continue to influence the society and Church. Hence, it is important that all those in the Church and society who are committed to gender justice need to set an example; and it is vital to create networks of people committed to gender justice. It is also important to remember that gender equality is not only essential to the dignity and wellbeing of women, but it is necessary to the dignity and happiness of men who now are pressured into inauthentic patterns of “masculinity” that are not compatible with a truly fulfilling personal identity.